Correlation between advanced glycation end-products and the expression of fatty inflammatory factors in type II diabetic cardiomyopathy - Zhengdong Guo; Donghui Huang; Xiange Tang; Jingjing Han; Jing Li (Biomolecules & Biomedicine, 2015)
Diabetic cardiomyopathy (DCM) is one of the most severe complications of diabetes without a clear pathogenesis. Th is study investigated the adiponectin (APN) and leptin levels in type II DCM, as well as their correlation with advanced glycation end-products (AGEs). From 2011–2013, 78 type II diabetes mellitus (T2DM) cases (40–65 years old) in the Taian region were randomly selected. Based on the results of colour Doppler ultrasonography and coronary angiography, the cases were divided into a simple T2DM group (40 cases) and a DCM group (38 cases). Forty healthy subjects were used as normal control (NC). An enzyme-linked immunosorbent assay was performed to determine the levels of fa tty infl ammatory factors such as APN, leptin and AGEs, and a correlation analysis was conducted. In the T2DM group, the APN levels were decreased but the leptin and AGE levels were signifi cantly increased compared to the NC group. In the DCM group, the APN levels were decreased but the leptin and AGE levels were signifi cantly increased (P<0.01) compared to the T2DM group. Th e AGE levels were positively correlated with disease progression and with fasting plasma glucose levels, glycated haemoglobin, insulin resistance and leptin, but were negatively correlated with APN levels. Additionally, the APN and leptin levels were independently related to the AGE levels. Fatty infl ammatory factors play a signifi cant role in the progression of both simple T2DM and DCM. Th e results of this study revealed the pathogenesis of DCM and indicated the potential signifi cance of AGEs in DCM prevention and treatment.